Chronic Pain Nursing Care for Elderly Gout Patients Using Warm Water Compress Therapy Combination Lemongrass and Ginger - Ndatang, Jefry Kabukut; Devi, Hilda Mazarina (Jurnal Surya, 2024)
Introduction: Uric acid is a normal substance found in the body and is the end result of purine metabolism, namely the result of the degradation of purine nucleotides which are important ingredients in the body as components of nucleic acids. The nursing problem that arises in elderly gout patients is chronic pain. The aim of this scientific work aims to explore nursing care for chronic pain in elderly gout patients with warm water compress therapy using lemongrass and ginger at RAAL Griya Asih Lawang.Methods: Using a case study design with nursing care. The subjects of this research were 3 elderly gout patients with chronic pain nursing problems for 3 days, with pain measurement using the Visual Analog Scale (VAS) and SLKI. and the targeted outcome criteria include the ability to complete activities, complaints of pain, protective attitudes, grimacing, restlessness and difficulty sleeping. The instrument used was the UNITRI gerontic nursing care format. Data was analyzed using the SMART method (Specific, Measurable, Achievable, Realistic, Time).Results: From the actions carried out on the three patients for 3 days, it was found that the chronic pain nursing problem in 3 patients was partially resolved with the following criteria: ability to complete activities increased, pain complaints decreased, protective attitude decreased, grimaces decreased, anxiety decreased, difficulty sleeping decreased.Conclusion: Due to limited time in conducting this research, which was only carried out for 3 days, it could affect the results of warm compresses using lemongrass and ginger which could only partially reduce pain complaints.Keywords: chronic pain, gout, warm water compress using lemongrass and ginger.